Anokhina T. A. Nomination tendencies of nonverbal lacunas in distant language discourses - Anokhina T. A. (Philological Treatises, 2020)
The article deals with the concept SILENCE and the language means of its nomination. Special attention is focused on the graphic means of exteriorization of the concept, its taxonomy, polyaspect and polyfunctional features (on the basis of the English and German discourses). Further perspectives of the researches are considered.